PERANCANGAN SISTEM REKOMENDASI PENJURUSAN PADA SEKOLAH MENENGAH KEJURUAN SANTO PAULUS MENGGUNAKAN METODE K-MEANS CLUSTERING - Isaias F.X.F.A. Felnditi; Desi Arisandi; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Santo Paulus Vocational School in Jakarta, is one of the Private Schools in Central Jakarta which holds majors for grade X (ten) students who will continue their studies to grade XI (eleven). The obstacle that is often found in the majors in SMK Santo Paulus Jakarta is the difficulty in determining which students meet the criteria to occupy certain majors. This is because the majors process is still done manually, so it requires quite a long time and is considered inappropriate. This study, purpose to the K-Means Clustering algorithm for the decision support system of student majors at SMK Santo Paulus Jakarta. K-Means Clustering algorithm can group data that has attributes and has a large amount of data, so that it can be utilized in the determination of student majors in accordance with students' academic abilities.Based on the results of the implementation of the K-Means Clustering algorithm for the majors decision support system, the conclusion that can be drawn is the K-Means-Clustering algorithm can be applied in the student majors decision support system.